Evaluating Environmental Variables in Determining Health Spending: A Case Study on Temperature, Rainfall and Environmental Quality Index in the Context of CHE (Catastrophic Health Expenditure) 10% - Fahmi Septiana Nugraha; Riki Relaksana; Akmal Fadhlurrahman; Rahmah Jaelani (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Catastrophic health expenditure (CHE) remains a pressing challenge in developing countries, including Indonesia, where households face significant financial risks from healthcare costs. Environmental factors such as temperature, rainfall, and environmental quality may exacerbate this burden, yet their impacts have not been fully explored in the Indonesian context. This study examines how these environmental variables influence CHE at the 10% threshold across 34 provinces during 2018-2019. Using spatial panel data regression, the analysis reveals that temperature has a non-linear effect on CHE: moderate increases raise health expenditures, but extreme levels tend to reduce them. Rainfall shows a diminishing effect, with initial increases linked to higher CHE, while excessive rainfall lessens the impact. In contrast, improvements in the Environmental Quality Index (EQI) significantly reduce CHE, highlighting the role of better air, water, and land conditions in alleviating household financial pressure. Spillover effects across provinces are minimal, suggesting limited indirect influence. The findings underscore the importance of integrating environmental policies with health financing strategies to mitigate the economic burden of healthcare.